Micromechanical testing for quantitative characterization of apparent slip system: Extinction of persistence of slip in carbon bearing Fe-3% Si. (15th July 2023) - Tanaka, Masaki; Takenaka, Masanori; Yamasaki, Shigeto; Morikawa, Tatsuya
Abstract: The effect of carbon on the persistence of the slip in Fe–3 mass% Si was investigated. We applied micro-sized cantilever bending tests to obtain ψ–χ relationships that enable quantitative analysis of the persistence of the slip. It was demonstrated that the result from decarburized specimens using this method is consistent with those obtained in previous studies from bulk-sized tensile test specimens. This novel method eliminates the difficulty of preparing bulk-sized single-crystal specimens for investigating the persistence of the slip. The persistence of the slip weakened in aged specimens containing 0.016 mass% C and disappeared in quenched specimens with the same carbon content, where wavy slip bands were observed. The reason for these changes in the macroscopically apparent slip plane is explained by the assumption that the frequency of nucleating kink-pair in the competitive {110} planes is a function of the resolved shear stress. Graphical abstract: Image, graphical abstract